Evaluation of the Absorbance and Transmittance of the Optical Light for Three Different Types of Composite Resin Stored in Artificial Saliva (in vitro study) - Rajaa T. Suliman (University of Mosul, College of Dentistry, 2017)
Aims: To evaluate the Absorbance and transmittance of the optical light for three different types of light activated dental composite resin stored in artificial saliva. Materials and Methods: 30 specimens were prepared from light activated composite resin and divided in to three groups, G1: 10 specimens prepared from Els, G2: 10 specimens prepared from Tetric n Ceram, G3: 10 specimens prepared from Solitaire2. Absorbance of the optical light measured using spectrophotometer. The specimens were evaluated after (zero,1,7,28) day immersion time in artificial saliva. Results: Statistical analysis shows significant difference at P ≤ 0.05 among tested groups at same immersion time, Solitaire 2 showed highest absorbance means compare to Tetric, Els specially after 1 day immersion in artificial saliva. No significant difference P> 0.05 in absorbance mean at various immersion time in artificial saliva for each group. Els shows low absorbance and highest transmittance percentage T% than Tetric and Solitaire composite resin. Conclusion: The Els extra composite resin has lowest absorbance and highest transmittance means for optical light, Solitaire2 showed more absorbance means with less amount of light transmittance through the composite resin compare to Tetric and Els. The performance of the experimented groups statistically not significant in terms of immersion time in artificial saliva.